Modern glacier dynamics in Mt. Tsambagarav in the Mongolian Altai Mountain Range - Davaagatan, Tuyagerel; Orkhonselenge, Alexander (Mongolian Geoscientist, 2020)
This study presents the modern glacier dynamics in Mt. Tsambagarav in the Mongolian Altai Mountain Range over the last four decades. This is the first review of this type of glacier dynamics for this massif. Changes in glacier area in Mt. Tsambagarav are estimated using normalized indexes (Normalized Difference Snow Index and Normalized Difference Principal Component Snow Index). Spatial distribution of the modern glaciers delineated with Landsat Multispectral Scanner (MSS: resolution of 80 m), Landsat Thematic Mapper (TM: resolution of 30 m) and Landsat Operational Land Imager (OLI: resolution of 30 m) imageries. Result shows that Mt. Tsambagarav has lost 51.7% of the glacier area from 132.24 km2 in 1977 to 63.92 km2 in 2017. The loss in glacier area for Mt. Tsambagarav during the last 40 years reflect the rapid response of the modern glacier to climate change, i.e., it is highly sensitive to solar insolation and/or rapidly rising local and regional mean annual temperatures. The remote sensing data and field survey suggest that the modern glaciers would be disappeared on a scale of decades. Rapid melting of the glacier in this massif contributes to surface water resources in western Mongolia. This study demonstrates the importance of spatial analysis in the remote area for understanding the context of changes in the modern glaciers.